A plate tectonic view from the top of the world. (21st February 2022) - Larson, Kyle P.; Cottle, John M.; Kylander‐Clark, Andrew; Lageson, David
Abstract: New U–Pb calcite geochronological analysis of shear veins in specimens collected from the summit pyramid of Mount Everest demonstrate that upper crustal deformation recorded in those rocks is Himalayan in age and was ongoing at 45.0 ± 5.4 Ma. This deformation precedes movement along the adjacent Qomolangma detachment by ~30 Myrs and coincides with metamorphism in nearby, structurally deeper, sillimanite‐migmatite gneisses and eclogite. The coeval record of deformation and metamorphism across all crustal levels further coincides with detachment of the Indian oceanic lithospheric slab, the inferred "main" collision and final closure of the Tethys ocean in multi‐collisional models of the Himalaya, and Eocene reorganization of tectonic plates in the South Pacific. This new dataset confirms that the summit rocks from Mount Everest preserve not only a complex, multi‐deformational record of Himalayan orogenesis, but also large‐scale changes in plate tectonics.